DEVELOPING A GAMIFICATION-BASED INSTRUCTIONAL MODULE TO IMPROVE STUDENTS’ READING COMPREHENSION - Ma'arip, Syamsul; Ummah, Inayatul; Setiawan, Dadan (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Reading comprehension is a fundamental skill that influences elementary students’ overall learning achievement; however, this ability often remains limited due to the use of less interactive teaching materials and teacher-centered instructional practices. This study aimed to develop a gamification-based teaching module and to examine its feasibility as well as its potential contribution to improving students’ reading comprehension. The research employed a Research and Development (R&D) design adapted from the Borg and Gall model through seven stages. The participants consisted of 25 fifth-grade students of Sekolah Indonesia Kota Kinabalu (SIKK), Sabah, Malaysia. Data were collected through interviews, observations, tests, and documentation, and were analyzed using expert validation, the Wilcoxon signed-rank test, and N-Gain analysis. The validation results indicated that the developed module met highly feasible criteria in terms of media, language, and content aspects. In addition, the comparison of pre-test and post-test scores showed a statistically significant increase in students’ reading comprehension, with an N-Gain score of 0.77 categorized as high. These findings suggest that the gamification-based module has promising potential to support students’ reading comprehension and learning engagement. Nevertheless, the interpretation of effectiveness is limited to the current sample context due to the absence of a control group and the relatively small number of participants. Therefore, this module may serve as a relevant instructional alternative in elementary Indonesian language learning, while further studies with broader experimental designs are recommended.